Limites de cloretos para a passivação de aços inoxidáveis ferríticos lean - Queiroz, Ana Luiza Lima (Universidade Federal de São Carlos, 2023)
Among the various classes of existing steels, stainless steels stand out in terms of corrosion resistance. Chromium is the main alloying element, and stainless steels are those with addition of Cr equal to or above 10.5% mass. However, several applications may not be corrosive enough to justify the use of conventional stainless steels, but excessively corrosive to carbon steels. In this context, steel compositions with contents between 6% and 10% have not yet been widely explored in terms of their corrosion resistance. Thus, the objective of this project is to evaluate the chloride concentration limits in which steels with a Cr content between 6 and 11% by weight behave like conventional stainless steels. Thermodynamic calculations were performed to guide the processing route of these alloys, called lean stainless steels, which were produced in a vacuum induction furnace and rolled, annealed and pickled. They were tested in three solutions with NaCl concentration ranging from 0.1 mol/L to 0.6 mol/L through the electrochemical techniques of potentiodynamic polarization and electrochemical impedance spectroscopy. Finally, the results obtained for lean steels were compared with those obtained for stainless steel UNS S41003 (410D), Cr content between 10.5% and 12.5%. From the electrochemical results it was observed that steels with 8%m. of Cr or less do not present a passive plateau under the tested conditions, they also have low polarization resistance (Rp < 10 kΩ.cm2) according to electrochemical impedance spectroscopy tests. At the lowest chloride concentration, steels with 9%m. of Cr or more presented a passive plateau and greater polarization resistance (Rp > 100 kΩ.cm2) and at intermediate and higher concentrations steels with 10%m. of Cr or more have a passive plateau and high polarization resistance.
Chloride limits for the passivation of lean ferritic stainless steels
Keywords: Passivação; Ligas Fe-Cr; Aço inoxidável; Aços lean; Stainless steel; Passivation; Fe-Cr alloys; Lean steels; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA